2006
DOI: 10.1212/01.wnl.0000220197.36849.1e
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in MELAS improved by l-arginine supplementation

Abstract: The authors evaluated endothelial function in patients with MELAS (mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke) by flow-mediated vasodilation (FMD) and found a significant decrease vs controls. Two years of supplementation with oral l-arginine, a nitric oxide precursor, significantly improved endothelial function to control levels and was harmonized with the normalized plasma levels of l-arginine in patients. l-Arginine therapy improved endothelial dysfunction and showed promise in trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(138 citation statements)
references
References 9 publications
6
131
0
Order By: Relevance
“…After 2 years of oral arginine, these patients showed significantly increased arginine-HCL stimulated dilation of their brachial arteries compared with similar studies at baseline [13]. They also had less severe and fewer admissions for strokelike episodes [14].…”
Section: Argininementioning
confidence: 53%
See 2 more Smart Citations
“…After 2 years of oral arginine, these patients showed significantly increased arginine-HCL stimulated dilation of their brachial arteries compared with similar studies at baseline [13]. They also had less severe and fewer admissions for strokelike episodes [14].…”
Section: Argininementioning
confidence: 53%
“…The results of these studies showed improved clinical recovery and neuroimaging (statistical parametric mapping-single proton emission computed tomography, SPM-SPECT) in a few patients who received arginine-HCl, as well as significantly increased plasma NO, citrulline, and cyclic guanosine monophosphate [12]. Separate acute studies showed that MELAS patients had lower diameter brachial arteries compared with control patients at baseline, which improved after administration of intravenous arginine-HCl, but not to the full extent of controls [13]. Two follow-up open-label clinical trials of arginine have been conducted or are awaiting recruitment, for which the results are yet available [16,18].…”
Section: Argininementioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that intravenously administered L-arginine improved acute stroke-like symptoms in MELAS patients (Koga et al 2005). Furthermore, long-term supplementation of oral L-arginine has been shown to improve endothelial dysfunction and potentially play a role in the prevention of stroke-like episodes in MELAS (Koga et al 2006). Similar to the MELAS stroke-like episodes, many patients with the POLG1 mutation and stroke have reported migrainous headache, seizures, and cortical blindness in association with the stroke.…”
Section: Similarity To Stroke In Melasmentioning
confidence: 99%
“…The pathogenesis of the stroke-like episodes that characterize MELAS syndrome remain unclear; however, vasoconstriction is likely involved, as well as altered brain vascular endothelial function [21,22]. L-arginine administration during the acute phase and prophylactically appears effective.…”
Section: Amino Acid Supplementsmentioning
confidence: 99%